Regulation of Myosin-5b by Rab11a and the Rab11 family interacting protein 2. Issue 1 (8th January 2019) - Ji, Huan-Hong; Yao, Lin-Lin; Liu, Chang; Li, Xiang-dong
Abstract : Mammalian myosin-5b (Myo5b) plays a critical role in the recycling of endosomes to the plasma membrane via the interactions with Rab11a and the Rab11 family interacting protein 2 (FIP2). However, it remains unclear on how Rab11a and FIP2 are coordinated in tethering Myo5b with the vesicles and activating the motor function of Myo5b. In the present study, we show that Rab11a binds to the globular tail domain (GTD) of Myo5b and this binding abolishes the head–GTD interaction of Myo5b, thus activating the motor function of Myo5b. On the other hand, FIP2 directly interacts with both Rab11a and the tail of Myo5b, and the binding of FIP2 to Myo5b does not affect Myo5b motor function. Moreover, Rab11a displays higher affinity to FIP2 than to Myo5b, suggesting that Rab11a binds preferentially to FIP2 than to Myo5b. Based on the current findings, we propose that the association of Myo5b with vesicles is mediated by FIP2, which bridges Myo5b and the membrane-bound Rab11a, whereas the motor function of Myo5b is regulated by Rab11a.